Gambaran Kejadian Stunting Pada Anak Usia Sekolah di Daerah Pertanian: Description Of Stunting Incidence In School-Age Children In Agricultural Area - Alfan Afandi (Universitas Ngudi Waluyo, 2023)
Stunting is an indicator of chronic malnutrition which describes a history of malnutrition that has occurred over a long period. An assessment of stunting risk factors, especially environmental factors in children, needs to be carried out considering that the child's growth period, especially elementary school-aged children, it is much influenced by the environment in which students live/work. This study aimed to describe the incidence of stunting in elementary school-age children in agricultural areas. This research is a descriptive observational study with a cross-sectional approach. The study was conducted at SD N 1 Kluwut with the research sample being all students who attended SDN 1 Kluwut. Observations on environmental factors were carried out on 10 children with stunting status who were randomly selected. Weight and height measurements using digital scales and a stadiometer. The research data were analyzed descriptively. The results showed that 14.5% of children were in a short category and 0.4% in a very short category at SD N 1 Kluwut. From the observations of 10 stunted children randomly selected, it was found that 7 of them came from parents with a farmer background where the children also participated in agricultural activities such as mritili, drying, and harvesting onions. The results of measuring nutritional intake also revealed that 10 respondents had quite good energy and protein intake. Keywords: stunted, child, environment ABSTRAK Stunting merupakan salah satu indikator adanya masalah kekurangan gizi kronis yang menggambarkan riwayat kekurangan gizi yang terjadi dalam jangka waktu yang lama, penilaian faktor resiko stunting terutama faktor lingkungan pada anak perlu dilakukan mengingat pada periode pertumbuhan anak terutama anak usia sekolah dasar banyak dipengaruhi oleh lingkungan dimana siswa tinggal/beraktfitas. Tujuan dari penelitian ini adalah untuk mengetahui gambaran kejadian stunting pada anak usia sekolah dasar di daerah pertanian. Penelitian ini merupakan penelitian observasional deskriptif dengan pendekata crossectional. Studi dilakukan di SD N 1 Kluwut dengan sampel penelitaian adalah seluruh siswa yang sekolah di SDN 1 Kluwut. Observasi terhadap faktor lingkungan dilakukan terhadap 10 anak dengan status stunting yang dipilih secara acak (random). Pengukuran berat badan dan tinggi badan menggunakan timbangan digital dan stadiometer. Data hasil penelitian dinalisis secara deskriptif. Hasil penelitian menunjukkan bahwa terdapat 14,5 % anak dengan kategori pendek dan 0,4 % kategori sangat pendek di SD N 1 Kluwut. Dari hasil observasi terhadap 10 anak stunting yang dipilih secara random diketahui 7 diantaranya berasal dari orang tua yang berlatar belakang sebagai seorang petani dimana anak-anak juga mengikuti aktifitas pertanian seperti mritili, menjemur dan memanen bawang. Hasil pengukuran asupan gizi juga diketahui 10 responden memiliki asupan energi dan protein cukup baik. Kata kunci: stuntig, anak, lingkungan